The Resilience of Non-Profit Organizations in the Funding Crisis: Learning from CRP Bangladesh’s Strategic Innovation in Prosthetics and Orthotics - Okki Adittio Ricatd Leviyan; Dasrun Hidayat; Kahar Mulyani (Technium Business and Management, 2026)
The termination of the International Committee of the Red Cross’ (ICRC) support in 2023 has made significant changes to the sustainability of prosthetic and orthotic (P&O) services at the Centre for the Rehabilitation of the Paralyzed (CRP) Bangladesh. This study aims to analyze how CRP adapts organizationally, diversifies funding, and strengthens partnerships after donor-exit. The research used a qualitative method with a case study design and interviewed nine informants from CRP Savar, CRP Mirpur, TMSS, as well as former ICRC staff. The results of the study show that organizational adaptation takes place through revision of policies and SOPs, material and cost efficiency, strengthening human resource capacity, and adjusting procurement systems and technology. The funding diversification strategy is carried out through increasing internal revenues (commercial units, high-tech services, and cross-subsidy mechanisms) as well as expanding external funding from governments, international NGOs, local donors, CSR, and individuals. On the partnership side, CRP strengthens existing collaborations, builds new networks, and enhances multi-donor transparency as a basis for public legitimacy. Overall, the study concludes that the sustainability of P&O CRP services is built through a combination of operational adaptation, funding innovation, and long-term partnership strategies, and makes a theoretical contribution to the study of nonprofit organization management in the donor-exit context.